MULTICENTER ANALYSIS OF THE EFFECT OF PHARMACISTS' EMPATHY ON MEDICATION ADHERENCE IN PATIENTS WITH CHRONIC DISEASES AT PUBLIC HEALTH CENTERS - Oliva Chrisna, Syamarel
Non-adherence has become a major concern in treating patients with chronic diseases as it can result in worsening disease, increasing health-related expenses, and even death. The lack of decent communication between physician and patient becomes one of the factors, including the lack of empathy. This study aims to evaluate whether empathy given by pharmacists is associated with patients’ medication adherence. The research was conducted at Puskesmas Ibrahim Adjie and Puskesmas Pasundan in Bandung as well as Puskesmas Cimahi Tengah in Cimahi from December 2023 to May 2024 with a cross-sectional method where standardized questionnaires were used. The questionnaires used in this study are the Consultation and Relational Empathy (CARE) questionnaire and the MARS-5 questionnaire. A total of 113 respondents were acquired where the average score for the CARE questionnaire was 33,018 ? 6,977 and the average score for the MARS- 5 questionnaire was 22,566 ? 3,367. A lot of the respondents were females aged between 55-74 with either hypertension or diabetes mellitus. Spearman’s correlation test revealed a significant positive correlation between empathy perceived by patients and medication adherence (p = 0,022; r = 0,215). No correlation is found between sociodemographic factors and medication adherence. However, the result showed that age (p = 0,006; r = -0,257), number of medicines taken (p = 0,038), and whether the patients have received counseling (p = 0,015) affect the perceived empathy by patients. Medication adherence in patients with chronic disease is influenced by the empathy they perceive during counseling, and the empathy perceived by patients is affected by the patient’s age and the number of medicines they consume, as well as the type of interaction between patients and pharmacists.